Pregnancy outcomes in patients with polycystic ovary syndrome who conceived after single thawed blastocyst transfer: a propensity score-matched study - Hui-Ying Jie; Xiu Zhou; Ming-Peng Zhao; Min Hu; Qing-Yun Mai; Can-Quan Zhou (BMC Pregnancy and Childbirth, 2022)
Abstract Background It remains unclear whether polycystic ovary syndrome (PCOS) is an independent risk factor for pregnancy complications in women undergoing assisted reproductive technology (ART) treatment. For the integrative treatment of PCOS patients, it is still important to investigate the pregnancy outcomes of PCOS patients after adjusting for potential biases, such as body mass index, embryo quality and endometrial preparation method. Methods This retrospective cohort study ultimately included a total of 336 PCOS patients who conceived after single thawed blastocyst transfer in the PCOS group and 2,325 patients in the control group from January 2018 to December 2020. A propensity score matching (PSM) model was used, and 336 PCOS patients were matched with 336 patients in the control group. Results Before PSM, no differences in the miscarriage rate, pregnancy complication rate, preterm birth rate, or live birth rate were found between the PCOS group and the control group. After PSM, the late miscarriage rate of the PCOS group was significantly higher than that of the control group (3.3% vs. 0.6%, P = 0.040), although the early miscarriage rates were similar (14.0% vs. 13.7%). The rates of pregnancy complications, preterm birth and live birth in the PCOS group were comparable to those in the matched control group (P = 0.080, P = 0.105, P = 0.109, respectively). The neonatal weights of male infants and female infants were similar between the two groups (P = 0.219, P = 0.169). Subgroup analysis showed that PCOS patients with homeostasis model assessment of insulin resistance (HOMA-IR) levels ≥ 2.49 had a significantly increased risk of preterm birth compared with those with HOMA-IR levels < 1.26 and 1.26 ≤ HOMA-IR levels < 2.49 (26.0% vs. 6.0% vs. 9.8%, P = 0.005). PCOS patients with total testosterone levels ≥ 0.7 ng/ml had a higher early miscarriage rate but a lower late miscarriage rate than those with total testosterone levels < 0.7 ng/ml (29.4% vs. 12.3%, 0% vs. 3.6%, respectively, P = 0.032). Conclusions PCOS is an independent risk factor for late miscarriage in patients conceived after a single thawed blastocyst transfer, even after adjusting for biases. Among PCOS patients, insulin resistance and hyperandrogenism are associated with a higher risk of preterm birth and early miscarriage, respectively.